COMMUNITY EMPOWERMENT BASED ON HEALTH AND PRODUCTIVITY IN AEK UNCIM VILLAGE, SOUTH TAPANULI - Ali Nurdin Siregar; Nursahara Nursahara; Fajar Fadli Batubara (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Aek Uncim Village faces public health challenges, particularly low environmental hygiene awareness and high tuberculosis prevalence. This Community Service Program (KKN) aims to improve health awareness and community productivity through a comprehensive approach that integrates four areas: academic, religious, arts-sports, and health thematic. Activities were conducted from September 26, 2025, to January 16, 2026, using participatory methods with normative and historical approaches. Data were collected through observation, interviews, pre-post tests, and documentation, then analyzed using descriptive quantitative and qualitative methods. Results show significant improvements: community knowledge about TB increased by 43.5% (from 44% to 87.5%), anti-bullying knowledge increased by 71% (from 52% to 89%), posyandu participation rose by 50% (from 52% to 78%), and elderly exercise participation reached 75%. The economic empowerment program successfully established 3 pilot locations for plant cultivation with potential income increases of 25-30%, 1 communal living pharmacy and 8 independent living pharmacies with 5 types of medicinal plants, and 15 families producing organic compost that reduced chemical fertilizer dependency by up to 40%. The program successfully increased community awareness of environmental hygiene and communicable disease prevention, with 89% of respondents reporting positive behavioral changes in environmental health maintenance and program sustainability reaching 85.7%.